Pemanfaatan Lingkungan Sekitar Sebagai Media Pembelajaran - Afan Chrislando (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
The lack of use of the surrounding environment as a learning media for students, where the teacher always considers that the only media or source of learning, but can be seen from the explanation of the theory, that the environment around children, a lot of information or symptoms that participants get not only students. The teacher can also feel the benefits of using the surrounding environment as a learning medium, can help teachers in delivering material that does not only occur in the classroom, but learns outside the classroom, and uses the environment as a source of learning, will make students know more about the environment around students.